An Analysis of Effect GSM Signal Type on Android-Based Vehicle Injector Response Time - Mira Esculenta Martawati; Fatkhur Rohman; Sugeng Hadi Susilo; Bagus Dwi Cahyo (International Journal on Advanced Science, Education, and Religion, 2022)
The crime of motor vehicle theft is increasing, the automotive industry continues to develop security systems to reduce the number of thefts that occur in Indonesia through the development of sophisticated features. The addition of a global positioning system (GPS) feature on a vehicle is an alternative to supporting a security system by providing vehicle location information when theft occurs. GPS provides location information by providing microcontroller input data. GPS on the vehicle becomes very important because with the GPS module the vehicle can be found by knowing an accurate location. However, the addition of a GPS module is often difficult to find because the distance changes frequently and it takes a long time to find it. The purpose of this paper is to detect vehicle position accurately using GPS U-Blox NEO 6M and to analyze the effect of GSM signal type on the response time of long-distance vehicle injectors based on android. The research method is data analysis to make conclusions, namely the two-way factor quantitative experimental method. The independent variables used are (1) different signal types, and (2) the distance from the signal source to the gasoline engine injector response time. The conclusion obtained is that vehicle position detection using GPS U-Blox NEO 6M is accurate with the results of data analysis shifting 8.3113 meters and the interaction between distance and GSM signal types has no significant effect with the results of data analysis from the three types of Telkomsel GSM signals which are the fastest with a distance of 200 meters from the signal source with a response time of 4.956 seconds and the slowest is XL at a distance of 500 meters from the signal source with a response time of 8.5 seconds. Keywords: Android-Based Vehicle Injector, GSM Signal Type, Vehicle Injector